2001
DOI: 10.1080/10473289.2001.10464254
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Real-Time Instruments Used To Monitor Airborne Particulate Matter

Abstract: Measurements collected using five real-time continuous airborne particle monitors were compared to measurements made using reference filter-based samplers at Bakersfield, CA, between December 2, 1998, and January 31, 1999. The purpose of this analysis was to evaluate the suitability of each instrument for use in a real-time continuous monitoring network designed to measure the mass of airborne particles with an aerodynamic diam less than 2.5 µm (PM 2.5 ) under wintertime conditions in the southern San Joaquin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(128 citation statements)
references
References 14 publications
3
124
0
Order By: Relevance
“…Impactors were used to perform the necessary size cut and the particle mass concentration was determined by measuring the intensity of the 901 scattering of light from a laser diode. However, as reported elsewhere (Ramachandran et al, 2000;Chung et al, 2001;Yanosky et al, 2002;Fitz et al, 2003), DustTrak measurements were generally higher than the integrated gravimetric method and to provide absolute concentrations comparable to other studies, PM 2.5 mass data reported here are from the Harvard Impactors. Data collected with the DustTrak were only used on a relative basis during window position tests, when real-time information was required.…”
Section: Instrumentationsupporting
confidence: 88%
“…Impactors were used to perform the necessary size cut and the particle mass concentration was determined by measuring the intensity of the 901 scattering of light from a laser diode. However, as reported elsewhere (Ramachandran et al, 2000;Chung et al, 2001;Yanosky et al, 2002;Fitz et al, 2003), DustTrak measurements were generally higher than the integrated gravimetric method and to provide absolute concentrations comparable to other studies, PM 2.5 mass data reported here are from the Harvard Impactors. Data collected with the DustTrak were only used on a relative basis during window position tests, when real-time information was required.…”
Section: Instrumentationsupporting
confidence: 88%
“…Continuous PM 2.5 , particulate matter with aerodynamic diameter, D a , less than 2.5 µm, mass concentrations measured using the CAMM and BAMs were evaluated by the BIIS project team (Chung et al 2001a). They found that 24-h PM 2.5 concentrations measured with both BAMs correlated well (R 2 ≥ 0.99) with results from a Federal Reference Method (FRM) sampler.…”
Section: Methodsmentioning
confidence: 78%
“…MOI samplers were operated simultaneous with ATOFMS instruments during 7 intensive operating periods (IOPs) (Chung et al 2001a(Chung et al , 2001b. The IOPs were on 14 January (BAK01), 15 January (BAK02), 16 January (BAK03), 19 January (BAK04), 21 January (BAK05), 22 January (BAK06), and 23 January (BAK07).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By volume, the standard consists of 1-3% particles with diameters less than 1 m, 36 -44% with diameters less than 4 m, 83-88% with diameters less than 7 m, and 97-100% with diameters less than 10 m. Niu et al 25 found that in comparing data from four DustTraks collocated in an indoor environment, the interinstrument variability was a reasonable 3%. Several authors have also reported that DustTrak measurements correlate well with filter-based measurements of diesel exhaust, 26 ambient urban particulate matter, 27 and indoor airborne particles, 25 though in all cases, investigators noted that the DustTrak deviated from filter-based measurements by a factor that depends on the nature of the aerosol measured. One shortcoming of using a nephelometer-style instrument is that light scattering response to changes in mass concentration can depend strongly on particle composition as well as particle size.…”
Section: Field Measurementsmentioning
confidence: 99%